1991
DOI: 10.2118/17767-pa
|View full text |Cite
|
Sign up to set email alerts
|

Simplified GERG Virial Equation for Field Use

Abstract: A GERG (Groupe EurQpeen de Recherches Gazieres) equation of state (EOS) is presented to calculate the compressibility factor of natural gases. The equation, which does not require detailed gas analysis, can predict the compressibility factor when three of the four following gas properties are known: the gross calorific value, the relative density, and the mole fractions of N 2 and CO 2 , The new equation, known as the SGERG-88 vi rial equation, is based on ideas presented in an earlier study. The new equation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 4 publications
7
42
0
Order By: Relevance
“…Jaeschke et al (7) (referred to as the GERG group) have reviewed the published measurements on carbon dioxide and concluded that the studies of Michels and Michels (8) and of Michels et al (9) represented the most reliable and extensive measurements. Brugge et al (10) compared their two more recent measurements (at 300 K and 320 K) with earlier work and demonstrated excellent agreement with Michels and Michels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jaeschke et al (7) (referred to as the GERG group) have reviewed the published measurements on carbon dioxide and concluded that the studies of Michels and Michels (8) and of Michels et al (9) represented the most reliable and extensive measurements. Brugge et al (10) compared their two more recent measurements (at 300 K and 320 K) with earlier work and demonstrated excellent agreement with Michels and Michels.…”
Section: Resultsmentioning
confidence: 99%
“…(8) Jaeschke et al (7) reviewed the reported measurements for CO 2 and generated the best-fit equation:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In figure 3, the calculated values for the cross second virial coefficient of the CH 4 -CO 2 molecule pair are compared with selected experimental data [47][48][49][50][51][52][53][54][55][56] and with the correlation of Dymond et al [57]. The data of Ng [48] were taken from reference [57].…”
Section: Ch 4 -Co 2 Molecule Pairmentioning
confidence: 99%
“…The error bars shown in the figure correspond to those given by the authors except for the reanalyzed data of Martin et al, for which we also reanalyzed the uncertainty. We used the reanalyzed data of Martin et al [51] as well as the data of Jaeschke et al [52] and of Iglesias-Silva et al [57] for temperatures from (220 to 400) K exhibits large negative deviations at low temperatures, reaching −14.5 cm 3 · mol −1 at 220 K. Nevertheless, the correlation is consistent with the calculated values within the expanded (k = 2) uncertainty estimates of Dymond et al [57].…”
Section: Ch 4 -Co 2 Molecule Pairmentioning
confidence: 99%